Multidrug Resistant Uropathogens among Urinary Tract Infections Patients: A Potential Public Health Hazard - Ashraf, Asfa; Iqbal, Muhammad Naeem (PSM Biological Research, 2024)
Urinary tract infections (UTI’s) account for the majority of hospital admissions globally and are the main cause of death and morbidity in patients with underlying comorbid illnesses. Multidrug resistance (MDR) is one of the most concerning health problems that arise from the improper and careless use of antibiotics, placing a significant strain on the healthcare system. In this issue, Iqbal et al. (2024) report the incidence of multidrug resistant bacterial isolates among UTI patients. The emergence of antimicrobial resistance in UTIs has presented a significant challenge to global health and urological infection treatment strategies. An optimized antimicrobial management program is necessary to provide efficient methods for treating UTI’s in diverse healthcare settings.